Earned Value Analysis Terhadap Waktu dan Biaya Pada Proyek Pembangunan Gedung Pasar Padang Panjang - Revi Lasmita; Mela Ardeline (Jurnal Kendali Teknik dan Sains, 2025)
Along with the population and economic growth of West Sumatra, especially in Padang Panjang City, West Padang Panjang District, the need for public facilities is urgently needed, one of which is the Padang Panjang market. In a project, planning and controlling costs and time is part of overall project management, especially at the implementation stage of the case study reviewed by researchers, namely the Padang Panjang market building construction project. In this research regarding time and cost control, the earned value method is one method that can monitor project performance in terms of time and cost. Which aims to determine project performance in terms of time and costs each week and predict the time and costs to complete the remaining work. So that we can get corrective actions to be taken next to progress the project. In this research, to obtain a basic basis for writing, secondary data collection is used as supporting data for the analysis of the results themselves. The analysis and discussion carried out were calculating the BCWS value, BCWP value and ACWP value in order to obtain the time variance value (SV), cost variance value (CV), calculating the productivity index, calculating project performance and calculating the estimated analysis of total project costs and completion time. The results of the research carried out are, the overall BCWS value of the Padang Panjang market project is IDR 96,213,315,046.3, for the BCWP value at the end of the 22nd week of review IDR 12,688,575,967, the ACWP value at the end of the 22nd week of review is IDR. 12,389,476,444.2 . As for the analysis results obtained from several existing indicators, the SPI value was 1.384 > 1, while the CPI was 1.003 > 1, which means that the project was accelerated in terms of schedule but incurred actual costs that were smaller than the work that had been carried out. The ETC value is IDR 84,134,151,328.9 and the EAC value is IDR 96,523,627,773.1, while the ECD value is 373 days for the project completion time.